2021
DOI: 10.1021/jacs.1c06036
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Palladium-Catalyzed Oxidative Sonogashira Carbonylation of Arylhydrazines and Alkynes to Ynones

Abstract: Oxidative carbonylation using carbon monoxide has evolved as an attractive tool to valuable carbonyl-containing compounds, while mixing CO with a stoichiometric amount of a chemical oxidant especially oxygen is hazardous and limits its application in scale-up synthesis. By employing anodic oxidation, we developed an electrochemical palladium-catalyzed oxidative carbonylation of arylhydrazines with alkynes, which is regarded as an alternative supplement of the carbonylative Sonogashira reaction. Combining an un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(34 citation statements)
references
References 68 publications
1
32
0
Order By: Relevance
“…For electrochemical borylation, phenyl radical A is formed via the oxidation of 3 on the anode with the aid of n Bu 4 NI. 34 The formation of product 2a from phenyl radical A is consistent with that of the photochemical process. Hydrogen gas evolves from hydrogen protons on the cathode.…”
supporting
confidence: 69%
“…For electrochemical borylation, phenyl radical A is formed via the oxidation of 3 on the anode with the aid of n Bu 4 NI. 34 The formation of product 2a from phenyl radical A is consistent with that of the photochemical process. Hydrogen gas evolves from hydrogen protons on the cathode.…”
supporting
confidence: 69%
“…In recent years, electrochemical synthesis has received increasing attention for its powerful ability to forge chemical bonds, presumably due to the advantages of no external stoichiometric chemical oxidants or reductants and milder conditions over the conventional approaches [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. As a result, we speculate that electrochemistry maybe provides a unique opportunity to facilitate the functionalization of azobenzene.…”
Section: Introductionmentioning
confidence: 99%
“…A further methodology for the electrochemical palladiumcatalyzed synthesis of ynones through a Sonogashira carbonylation mechanism was presented this year. 257 Wu and Zeng et al demonstrated the possibility to achieve the carbonylation of alkynes and arylhydrazines in an undivided cell with constant current mode, without the need for external oxidants or oxygen. A carbon felt anode and a graphite rod cathode under 1.5 mA current were employed, leading to a range of valuable ynones.…”
Section: Carbonylationmentioning
confidence: 99%